2018
DOI: 10.1016/j.triboint.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

CFD modeling compared to temperature and friction measurements of an EHL line contact

Abstract: In this paper, predictions from CFD modeling are compared against measurements of surface temperatures and friction for an EHL line contact lubricated with the fluid Santotrac 50. Two slide-to-roll-ratios (SRR), 50% and 100%, and entrainment velocities ranging from 0.211 to 1.13 m/s are considered. Very good agreement is shown for the 50% SRR cases, with only a 3% deviation in friction coefficient values. At 100% SRR, the deviation in friction increases to 3-7% which is attributed to deficiencies in the modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…This indicates that the choice of a rheological model and/or lubricant properties, at higher pressure levels, can cause significant deviation between numerical simulations and experimental measurements. This is in agreement with the recent study by Hartinger [25], who concluded that at the pressure of about 0.6 GPa, his CFD model of the EHL line contact problem overestimates shear-thinning effect on viscosity when compared to experimental measurements of friction and surface temperatures.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This indicates that the choice of a rheological model and/or lubricant properties, at higher pressure levels, can cause significant deviation between numerical simulations and experimental measurements. This is in agreement with the recent study by Hartinger [25], who concluded that at the pressure of about 0.6 GPa, his CFD model of the EHL line contact problem overestimates shear-thinning effect on viscosity when compared to experimental measurements of friction and surface temperatures.…”
Section: Discussionsupporting
confidence: 92%
“…where τ 0 is the Eyring stress that denotes the threshold where the Newtonian fluid behavior ends and the non-Newtonian fluid behavior starts. To avoid division by zero, instead of η 0 in Equation (29) Hartinger [25] suggests using the Houpert equation (Equation (25)). In addition, to avoid numerical error during simulation, Hartinger also recommends using the Ree-Eyring model only if strain rate is larger than an arbitrarily chosen minimum value of .…”
Section: Rheological Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In parallel to the popular numerical solver based on finite difference discretization, many researchers rely on the finite element method (FEM) to solve the equations involved in lubrication and solid contact [590,599,611], and CFD-based commercial software has become a popular tool in analysis of EHL, which could provide critical information for across-film distributions of velocity, temperature, and viscosity [597,612].…”
Section: Other Developments and Applicationsmentioning
confidence: 99%